Quality Education in Singapore: Bridging Teacher Leadership with Teacher Wellbeing - Chua, Catherine Siew Kheng; Soo, Li Mei Johannah; Chng, Hui Shi Elisa (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2025)
Although there is a growing body of research on teachers’ wellbeing, research on the relationship between teacher wellbeing and leadership roles in educational contexts is limited. Improved teacher wellbeing encourages teachers to engage in leadership roles, which affects student outcomes. This article discusses the dynamic symbiotic relationship between teacher leadership and teacher wellbeing. It posits that optimizing teacher wellbeing will increase teachers’ willingness and ability to take on more formal and informal leadership positions in schools for a sustained period. Utilizing human capital theory to illustrate the importance of investing in teachers’ physical, emotional, and cognitive states, this article proposes a “CEP Power-Up” decentralized-intentional approach encompassing four strategies to enhance schoollevel teacher wellbeing, leading to an uptake of leadership positions in Singapore schools.